Obliczanie strat hydraulicznych w przewodach czynnych sieci wodociągowych - Lewicki, Zbigniew (Zielona Góra: Uniwersytet Zielonogórski)
The problem of the increasing resistance of water - pipe network in the course of their exploitation and the review and analysis of empirical formulas whih to calculation resistance coefficient are used, is presented. A new calculation method of the hydraulic losses in exploited water - pipe network is described.
Keywords: sieć wodociągowa; straty hydrauliczne